Learning about inequality and demand for redistribution A meta-analysis of in-survey informational experiments - Ciani, ‪Emanuele (OECD Publishing, 2021)
A growing body of literature studies the effect of providing information about inequality to respondents of surveys on their preferences for redistribution. We provide a meta-analysis combining the results from 84 information treatments coming from 36 studies in Economics, Political Science, Psychology and Sociology. This meta-analysis complements and informs a broader project on perceptions of inequality and preferences for redistribution ( Does Inequality Matter? How People Perceive Economic Disparities and Social Mobility , OECD publishing, Paris, 2021). In the meta-analysis, we focus on in-survey experiments where a randomly selected group of respondents receive either information about the overall extent of inequalities, or about their position in the income distribution. The results show that providing information on inequality has a sizeable impact on people's perceptions and concerns about inequality, but a rather small effect on their demand for redistribution. Inspecting the heterogeneity across treatments and outcomes helps explaining the small average effect on demand for redistribution, but the evidence is not yet conclusive about the potential explanations. We further show that correcting respondents' misperceptions about their own position in the income distribution increases the preferences for redistribution for those who previously overestimated their position and decreases it for those who underestimated, although the effects are, on average, small
Keywords: Social Issues/Migration/Health